1979
DOI: 10.1136/gut.20.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde brush cytology in patients with primary and secondary malignancies of the pancreas.

Abstract: 25 October 1978 because of obvious changes due to pancreatic carcinoma (n = 12) beyond the reach of the brush device, technical difficulties (n = 11), or lack of cytological service or equipment to perform cytology (n = 5).Ductal abnormalities were demonstrated by ERCP in all patients (Fig. 1), and were strongly suggestive of malignancy in 58 cases and uncertain in 11 patients. Specimens for histological examination were obtained during surgery in 45 cases and at necropsy in 24 cases. In 12 patients the mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 6 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…In this study, 5 of 9 cases (56%) with carcinoma were correctly diagnosed by Papanicolaou staining in conjunction with ERPDB. Some previous studies have reported that the overall accuracy using endoscopic aspiration cytology ranges from 19‐92% 10‐12. The current study observations indicated that the range of overall accuracy using conventional cytology was not satisfactory, and may be dependent on the interpretation of each pathologist.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, 5 of 9 cases (56%) with carcinoma were correctly diagnosed by Papanicolaou staining in conjunction with ERPDB. Some previous studies have reported that the overall accuracy using endoscopic aspiration cytology ranges from 19‐92% 10‐12. The current study observations indicated that the range of overall accuracy using conventional cytology was not satisfactory, and may be dependent on the interpretation of each pathologist.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, cytologic confirmation using radiographic findings has been required to distinguish benign from malignant MPT in cases of MPT of the pancreas. The accuracy of conventional cytologic examination of pancreatic duct brushing samples or pancreatic juice collected during endoscopic retrograde pancreatography (ERP) is not satisfactory 10‐12…”
mentioning
confidence: 99%
“…The sensitivities of the CB method (50%) and smear cytology (39%) for malignant diseases in the present study are unsatisfactory but seem to be quite reasonable. The reported sensitivities of pancreatic juice cytology for pancreatic cancer even with administration of secretin were not satisfactory either, from 30% to 79% 8,13–20 . The sensitivity of pancreatic juice cytology by direct suction without giving secretin has been reported to be only 11.1% 17…”
Section: Discussionmentioning
confidence: 97%
“…Although brush cytology was expected to be an ideal method for obtaining cytological specimens from pancreatic duct strictures, its diagnostic sensitivities for pancreatic cancer have been reported to be 30% to 85% 8,16,24–31 …”
Section: Discussionmentioning
confidence: 99%
“…There are several tissue sampling methods for pancreatic lesions, such as (1) a core or wedge biopsy [1], (2) fine needle aspiration (FNA) [2], and (3) collection of pancreatic juice by direct suction, washing, or brushing during endoscopic retrograde cholangiopancreatography (ERCP) [1,3,4]. Among these sampling methods, FNA of the pancreas under US, CT, or EUS guidance has become established as the most reliable and safe procedure.…”
Section: Introductionmentioning
confidence: 99%